Uncertainty - Zygmunt Bauman’s Basic Ethical-Anthropological Category. - Kmiecikowski, Waldemar (Filozofia Chrześcijańska, 2011)
The article centers around Bauman’s category of uncertainty and presents its ethical and anthropological contexts. The author also makes an attempt to set human drama in onthological sphere. Post-modern man is deprived of solid moral indicators and has constant doubts about the rightness of his choices. Ethical-anthropological uncertainty is a sign of onthological instability and it seems to be the consequence of absurd and irrationality immanent to Bauman’s structure of being. Polish post-modernist does not say much explicite about being which is undoubtedly aporetical.